2015
DOI: 10.1007/s11356-015-4772-4
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study testing a European human biomonitoring framework for biomarkers of chemical exposure in children and their mothers: experiences in the UK

Abstract: Exposure to a number of environmental chemicals in UK mothers and children has been assessed as part of the European biomonitoring pilot study, Demonstration of a Study to Coordinate and Perform Human Biomonitoring on a European Scale (DEMOCOPHES). For the Europeanfunded project, 17 countries tested the biomonitoring guidelines and protocols developed by COPHES. The results from the pilot study in the UK are presented; 21 school children aged 6-11 years old and their mothers provided hair samples to measure me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…The median specific-gravity-adjusted urinary cadmium concentration was 0.06 μg/L (5%, 95%: 0.02, 0.17 μg/L). This is similar to levels reported for U.S. school children participating in the 1999-2004 NHANES (median 0.078 for 6-7 y-olds (Ciesielski et al, 2012), higher than in Danish children (median 0.021 μg/L), but lower than in children from several European countries (median ranges 0.14 -0.38 μg/L) (Aguilera et al, 2010;Exley et al, 2015;Fucic et al, 2015;Molina-Villalba et al, 2015;Protano et al, 2016;Roca et al, 2016) or Mexico (median 0.14 μg/L) (Moynihan et al, 2017) and especially lower than in children with rice-based diets, for example, 0.30 μg/L in 5 year-old rural Bangladeshi children (Kippler et al, 2010). We found no difference in urinary cadmium between girls and boys.…”
Section: Discussionsupporting
confidence: 86%
“…The median specific-gravity-adjusted urinary cadmium concentration was 0.06 μg/L (5%, 95%: 0.02, 0.17 μg/L). This is similar to levels reported for U.S. school children participating in the 1999-2004 NHANES (median 0.078 for 6-7 y-olds (Ciesielski et al, 2012), higher than in Danish children (median 0.021 μg/L), but lower than in children from several European countries (median ranges 0.14 -0.38 μg/L) (Aguilera et al, 2010;Exley et al, 2015;Fucic et al, 2015;Molina-Villalba et al, 2015;Protano et al, 2016;Roca et al, 2016) or Mexico (median 0.14 μg/L) (Moynihan et al, 2017) and especially lower than in children with rice-based diets, for example, 0.30 μg/L in 5 year-old rural Bangladeshi children (Kippler et al, 2010). We found no difference in urinary cadmium between girls and boys.…”
Section: Discussionsupporting
confidence: 86%
“…Younger children in Ireland (aged 5–8 years) were at higher risk than older children (aged 9–11 years) for all compounds, apart from MEP (and MEHP which was the same concentration in both age groups). Higher concentrations of phthalate compounds were also found in younger children in Germany when compared to older children [ 18 ], and in the UK [ 19 ]. A similar pattern was also noted in the DEMOCOPHES cohort, where younger children again had higher concentrations of all compounds apart from MEP [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of a consistent pattern for concentrations of MiBP and MEP in other studies. Studies of children in the UK [ 19 ], Germany [ 15 ], Austria [ 20 ], and the overall DEMOCOPHES cohort found higher concentrations for MiBP in children than MEP [ 13 ]. In contrast, other studies from Austria [ 21 ] and the USA [ 17 ] found higher concentrations of MEP.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in biomonitoring studies, children and adults are exposed to a large number of environmental chemicals across the life span (Aylward et al 2013; CDC 2012; Exley et al 2015; Frederiksen et al 2014). Many are potentially toxic, but little is known about health effects from exposure to complex mixtures (Carlin et al 2013; Claus Henn et al 2014; Goodson et al 2015; Grandjean and Landrigan 2014; Johns et al 2012).…”
Section: Introductionmentioning
confidence: 99%